ANALISIS PENGARUH EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN KARTU PRABAYAR IM3 ( Studi Pada Mahasiswa S1 Ekonomika dan Bisnis Undip Semarang ) - Niti Ibrahim, Galuh; Khasanah, Imroatul (Faculty of Economics and Business Diponegoro University, 2013)
Purchasing decision is a decision as an act of ownership of two or more alternative choices. Many factors can influence the purchasing decisions of consumers to a product, such as brand awareness, brand associations and quality perception. Consumer purchasing decisions can be made to the number of products, one of which is a prepaid card IM3. The selected object is a product of cellular IM3 Indosat card ranked as the market share is still IM3 prepaid cards under other brands that sympathy and the percentage decline in market share occurred in 2009-2011.The purpose of this study was to analyze the effect of brand awareness, brand associations and quality perception on purchase decisions.The population in this study were students of Economics and Business Undip S1, Jl. Tembalang, Semarang using Prepaid Card IM3. Samples taken 100 respondents. Sampling technique in this study was done by using simple random sampling. Is the primary data type. Methods of data collection using questionnaires. The analysis technique used is multiple regression.Results of analysis using SPSS Version 13 showed that brand awareness significantly influence the purchase decision. Brand associations have a significant effect on purchasing decisions. Perceived quality significantly influence the purchase decision. Therefore, the implications suggested in this study is Indosat should be developing a wider 3G network and expand the network in the cities that exist in the area, although it is done in stages. Make the size larger image and slogan slogan more attractive for consumers interested in having. By adding power to the BTS (Base Transceiver Station) so that it can be strengthened in receiving and distributing signals.